PENCIPTAAN BUKU FOTOGRAFI ESAI PLURALISME AGAMA DI BALI SEBAGAI UPAYA MENINGKATKAN KESADARAN MASYARAKAT DALAM TOLERANSI - Haidar, Muhammad; Budihardjo, Hardman; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract: Tolerance in etymology means a allow the attitude of mutual respect and beliefs of others without requiring approval. The cultural diversity of indonesia has many and various religions in indonesia and tolerance is needed to make indonesia as a country with strong. The number of cases of intolerance that occurred in indonesia should be the subject of tolerance that can be a very valuable to the nation. Indonesia, as a country that had enough of a difference, from the racial diversities, the key, and language. Bali being one example of regions in indonesia that presents diverse culture. Tolerance that occurs in bali so strong that deserve to be used as an example for indonesian. Therefore, it is a book about what the media tolerance in fact, it can increase the society awareness in bertoleransi. The study is done with a qualitative studies by taking the interview observation, documentation and literature to obtain the data is done as a supporter of the concept of design. Book served is shaped photographic book essay so that people can see clearly through some of the pictures that will be displayed.Â Keywords: Creation, Books of Photography Essay.